Management of Chronic Pain Associated with Small Fiber Neuropathy Secondary to SARS-CoV-2 - Anirudh Bhimavarapu; Hana Mucevic; Sadiq Rahman; Amruta Desai (International Journal of Translational Medicine)
Neuropathic pain has emerged as a significant concern for patients dealing with persistent post-COVID-19 symptoms. Small fiber neuropathy (SFN) has been identified as a potential underlying mechanism contributing to long-term pain in these patients. Despite an increasing body of evidence associating post-COVID-19 SFN with immune dysregulation and neuroinflammation, the exact pathophysiology and optimal treatment remains unclear. This review aims to explore the pathophysiology, diagnosis, proposed mechanisms, and treatment of post-COVID-19 SFN. A comprehensive literature review was conducted, examining studies on SFN, as well as SFN in the context of COVID-19, including clinical manifestations, diagnostic criteria, and potential treatment modalities. Evidence was gathered from case studies, observational reports, and clinical trials addressing post-COVID-19 neuropathy and SFN. SFN in long COVID presents a heterogeneous range of sensory and autonomic symptoms. Diagnosis relies on clinical evaluation, quantitative sensory testing, and confirmatory skin biopsy. Proposed mechanisms include autoimmune dysregulation, molecular mimicry, direct viral invasion of neural structures, and inflammatory responses. Pharmacological treatments—such as gabapentin, antidepressants, and corticosteroids—have demonstrated symptom relief, while immunomodulatory therapies show promise in immune-mediated cases. Non-pharmacological strategies warrant further investigation. Post-COVID-19 SFN represents a complex and multifactorial condition requiring a multidisciplinary approach to diagnosis and management. While merging evidence supports immune-mediated pathogenesis, further research is needed to establish definitive mechanisms and optimize targeted therapeutic strategies. Continued investigation into post-COVID-19 SFN will be crucial in addressing the long-term neurological sequelae of SARS-CoV-2 infection.